Carbon Stocks from Peat Swamp Forest and Oil Palm Plantation in Central Kalimantan, Indonesia - Novita, N; Kauffman, J.B.; Hergoualc'h, Kristell; Murdiyarso, D.; Tryanto, D.H.; Jupesta, J. (Springer, 2021)
Conserving high carbon density tropical peat forests is one of the most cost-efficient strategies for climate change mitigation at national and global levels. Over past decades, large areas of tropical peat forests have been converted to oil palm plantation in Indonesia resulting in significant carbon emissions into the atmosphere. Here, we quantified the ecosystem carbon stocks in a total of six sites: two primary peat swamp forest sites, one secondary peat swamp forest site, and three young oil palm plantation sites in Tanjung Puting, Central Kalimantan, Indonesia. We further determined potential carbon emissions from vegetation change due to peat swamp forest conversion to oil palm plantation. The mean total ecosystem carbon stock of primary and secondary peat swamp forests were 1770 ± 123 Mg C/ha and 533 ± 49 Mg C/ha, respectively. In contrast, the mean carbon stock of oil palm plantations was 759 ± 87 Mg C/ha or 42% of peat swamp forests. The ratio of the aboveground to belowground C stock was highest in secondary forest with an estimated value of 0.48, followed by primary forest at 0.19 and oil palm plantation at 0.04. Using a stock difference approach, we estimated potential carbon emissions from vegetation change resulting from the conversion of primary peat swamp forest to oil palm plantation of 640 ± 114 Mg CO2/ha. Finally, while restoring peatlands is important, avoiding peat conversion is imperative for Indonesia’s climate change mitigation effort.